Restricted and repetitive behavior in children with autism during the first three years of life: A systematic review - Chaxiong, Pang; Dimian, Adele F.; Wolff, Jason J. (Frontiers in Psychology, 2022)
Restricted and repetitive behavior (RRB) is a core diagnostic feature of autism spectrum disorder (ASD). Previous research shows that RRB is prevalent early in life and observed in neurotypical development as well. Less is known, however, about early RRB patterns, developmental trajectories, and the relation to outcomes for autistic children. The purpose of this systematic review was to synthesize findings from studies examining RRB in autistic children from birth through age three. A detailed protocol was designed a priori based on PRISMA guidelines for systematic reviews. From the published literature, forty-one peer reviewed journal articles were identified and included in this review. Our synthesis of the literature suggests that differences in RRB are evident prior to age two in children with or who go onto be diagnosed with autism. These differences were evident for both frequency and intensity of RRB across multiple topographies. There were mixed results regarding functional outcomes associated with early RRB, such as cognitive and adaptive behavior, though relations appeared to become stronger as children aged beyond toddlerhood. Notably, level of RRB appears unrelated to autism severity in young autistic children. A wide range of RRB have been reported to be elevated in autistic children during the first years of life, including repetitive motor behaviors, atypical sensory behaviors, insistence on sameness, and self-injurious behaviors. In contrast to studies of older children, RRB in very young autistic children do not appear to be associated with functional outcomes but may be valuable to include in early screening efforts.